Specialized molecular pathways drive the formation of light-scattering assemblies in leucophores - Yuval Barzilay; Zohar Eyal; Yael Noy; Neta Varsano; Tsviya Olender; Sourabh Bera; Tali Lerer-Goldshtein; Merav Kedmi; Ziv Porat; Iddo Pinkas; Smadar Levin-Zaidman; Nili Dezorella; et al. (Proceedings of the National Academy of Sciences, 2025)
Pigmentation plays a vital role in the survival of organisms, supporting functions such as camouflage, communication, and mate attraction. In vertebrates, these functions are mediated by specialized pigment cells known as chromatophores of which, uric acid crystal–forming leucophores remain the least understood, with little known about their molecular mechanisms. A key question in pigment cell biology is whether different crystal chemistries require distinct molecular pathways, or whether similar cellular processes drive the formation of diverse crystals. This study was designed to unravel the uncharacterized process of uric acid crystallization in leucophores and compare them to guanine crystal formation in iridophores and pterin formation in xanthophores. The results of our transcriptomic, ultrastructural, and metabolomic analyses, demonstrate that leucophores share molecular pathways with iridophores, particularly those connected to organelle organization and purine metabolism, but express discrete genes involved in uric acid biosynthesis and storage. Additionally, leucophores share intracellular trafficking and pterin biosynthesis genes with xanthophores, suggesting universally conserved processes. Ultrastructural studies reveal star-like fibrous structures in leucosomes, which likely serve as scaffolds for unique one-dimensional uric acid assemblies that radiate from the core and act as efficient light scatterers. These findings provide insights into leucophore cell biology and the specialized mechanisms driving molecular crystalline assembly, and reveal that while some cellular processes are conserved, the specific chemistry of each crystal type drives the evolution of distinct molecular pathways.